A cross-sectional study of malaria transmission in suggests the existence of a potential bridge vector susceptible of ensuring the transfer of simian malaria parasites to humans - Longo-Pendy, Neil-Michel; Boundenga, Larson; Makanga, Boris Kevin; Mbou-Boutambe, Clark; Bouafou, Lemonde; Akone-Ella, Ousmane; Nkoghe-Nkoghe, Lynda Chancelya; Lekana-Douki, Sonia; Lekana-Douki, Jean-Bernard; Kengne, Pierre (Frontiers in Ecology and Evolution, 2023)
Despite all the efforts made to control or even eliminate malaria, the disease continues to claim the highest number of victims in the world and Sub-Saharan countries bear the heaviest burden. The lack of knowledge of the role of various protagonists involved in the transmission of this parasitic disease, such as mosquito vectors and the plasmodial species they transmit as well as the host species they infect in a locality, constitutes one of the main causes of the persistence of malaria. In Gabon, in several areas, entomological data on malaria transmission remain poorly known. Thus, this study aimed to determine the diversity of Anopheles involved in malaria transmission in different environments of the province of Nyanga in southwest Gabon. For this, an entomological study was carried out in the four main localities of the province of Nyanga to provide answers to these shortcomings. Mosquitoes were collected over several nights using the human landing catch method. The identification of Anopheles and malaria parasites circulating in the different sites was achieved by combining morphological and molecular analysis tools. A total of five hundred and ninety-one (591) mosquitoes belonging to the Culicidae family were collected. From this collection of adult mosquitoes, nine species of Anopheles mosquitoes notably species of the Anopheles nili complex (53.46%) followed by those of Anopheles gambiae complex (22.01%), Anopheles funestus group (18.24%), Anopheles moucheti complex (5.66%) and Anopheles hancocki (0.63%). Approximately 18 percent of these Anopheles species were infected with Plasmodium spp. Anopheles funestus, known to be involved in malaria transmission to humans, and An. moucheti-like, recently discovered in Gabon, and whose status in Plasmodium transmission is not yet elucidated, were found to be infected with great ape Plasmodium. Our results raise the question of the potential switch of simian malaria parasites to humans. If these observations are confirmed in the future, and the infective capacity of the bridge vectors is demonstrated, this new situation could ultimately constitute an obstacle to progress in the fight against malaria.